Plasma Free Fatty Acids and Risk of Stroke in the Cardiovascular Health Study. Issue 7 (October 2014) - Khawaja, Owais; Maziarz, Marlena; Biggs, Mary L.; Longstreth, William T.; Ix, Joachim H.; Kizer, Jorge R.; Zieman, Susan; Tracy, Russell P.; Mozaffarian, Dariush; Mukamal, Kenneth J.; Siscovick, David S.; Djoussé, Luc
Background: Although free fatty acids have been positively associated with risk factors for stroke, the role of plasma free fatty acids in the development of stroke has not been elucidated in older adults. Aims: We sought to examine the association between plasma free fatty acids and incident stroke. Methods: Prospective cohort of 4369 men and women ⩾65 years of age in the Cardiovascular Health Study. Plasma levels of free fatty acids were measured at the 1992–1993 examination and stroke events were adjudicated by a committee of experts including neurologists and neuroradiologists. Cox regression was used to estimate the relative risk of stroke associated with free fatty acids concentrations. Results: The average age among participants was 75 ± 5·2 years. During a median follow-up of 11·4 years, 732 incident strokes occurred. The crude incidence rates of stroke were 14·5, 14·9, and 17·6 per 1000 person-years across increasing tertiles of plasma free fatty acids. The adjusted hazard ratio (95% confidence interval) for incident stroke was 1·05 (0·97–1·14) per standard deviation increase in plasma free fatty acids. Restriction to ischemic stroke did not alter the results [hazard ratio (95% confidence interval): 1·04 (0·96–1·14) per standard deviation higher free fatty acids], and there was no effect modification by adiposity (P interaction = 0–18) or by diabetes (P interaction = 0·15). Conclusion: Our data did not show an association of plasma free fatty acids with incident stroke among community dwelling older adults.